2017
DOI: 10.1200/jco.2017.35.15_suppl.6501
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive technology addressing optimal cancer clinical trial matching and protocol feasibility in a community cancer practice.

Abstract: 6501 Background: IBM Watson for Clinical Trial Matching (CTM) is a cognitive computing solution that uses natural language processing (NLP) to help increase the efficiency and accuracy of the clinical trial matching process. This solution helps providers locate suitable protocols for their patients by reading the trial criteria and matching it to the structured and unstructured patient characteristics when integrated with the Electronic Medical Record (EMR). It is also designed to determine which sites have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…CTM uses natural language processing (NLP) to ingest trial and patient information from unstructured sources and matches patients to trials for which they might be eligible through machine learning (ML) techniques. Previous studies have shown that CTM 10 can reduce the screening time for clinical trials and increase trial enrollment. 3 …”
Section: Background and Significancementioning
confidence: 99%
“…CTM uses natural language processing (NLP) to ingest trial and patient information from unstructured sources and matches patients to trials for which they might be eligible through machine learning (ML) techniques. Previous studies have shown that CTM 10 can reduce the screening time for clinical trials and increase trial enrollment. 3 …”
Section: Background and Significancementioning
confidence: 99%
“…Researchers have developed NLP models for a variety of EHR use-cases, from extracting physician-reported pain data from oncologic consultation notes, to identification of potential clinical trial participants by way of extracting inclusion and exclusion criteria. (14,15) Given its initial release and limited availability through a restricted-access program requiring formal application and approval, health care applications of GPT-3 remain sparse.…”
Section: Existing Health Care Applications Of Gpt-3mentioning
confidence: 99%
“…Therefore, an automated and efficient approach toward this process is highly welcome. The IBM Watson for Clinical Trial Matching (CTM), an NLP-based clinical trial coordinator, achieved a significant reduction in time of 86 min compared to a human coordinator, in processing 90 patients against 3 breast cancer protocols [24]. Another NLP model using semantically enriched document representation has also shown promising outcomes, with a micro-F1-Score of 84% for 13 different eligibility criteria [25 ▪ ].…”
Section: Deep Learning-based Natural Language Processing In Healthcarementioning
confidence: 99%